The effects of a multi-ingredient supplement on markers of muscle damage and inflammation following downhill running in females. Issue 1 (December 2016) - Köhne, Jessica; Ormsbee, Michael; McKune, Andrew
Abstract Background The effects of a multi-ingredient performance supplement (MIPS) on markers of inflammation and muscle damage, perceived soreness and lower limb performance are unknown in endurance-trained female athletes. The purpose of this study was to determine the impact of MIPS (NO-Shotgun®) pre-loaded 4 weeks prior to a single-bout of downhill running (DHR) on hsC-Reactive Protein (hsCRP), interleukin (IL)-6, creatine kinase (CK), muscle soreness, lower limb circumferences and performance. Method Trained female runners (n = 8; 29 ± 5.9 years) (VO2max : ≥ 50 ml-1 .kg-1 .min-1, midfollicular phase (7-11 days post-menses) were randomly assigned in a double-blind manner into two groups: MIPS (n = 4) ingested one serving of NO Shotgun daily for 28 days prior to DHR and 30 min prior to all post-testing visits; Control (CON) (n = 4) consumed an isocaloric maltodextrin placebo in an identical manner to MIPS. hsCRP, IL-6, CK, perceived soreness, limb circumferences, and performance measures (flexibility, squat jump peak power) were tested on 5 occasions; immediately before (PRE), immediately post-DHR, 24, 48 and 72 h post-DHR. Results There were main effects of time for CK (p = 0.05), pain pressure threshold (right tibialis anterior (p = 0.010), right biceps femoris (p = 0.01), and left iliotibial band (ITB) (p = 0.05) across all time points), and maximum squat jump power (p = 0.04). Compared with 24 h post-DHR, maximum squat jump power was significantly lower at 48 h post-DHR (p = 0.05). Lower body perceived soreness was significantly increased at 24 h (p = 0.02) and baseline to 48 h (p = 0.02) post DHR. IL-6 peaked immediately post-DHR (p = 0.03) and hsCRP peaked at 24 h post-DHR (p = 0.06). Calculation of effect sizes indicated a moderate attenuation of hsCRP in MIPS at 72 h post-DHR. Conclusions Consumption of MIPS for 4 weeks prior to a single bout of DHR attenuated inflammation three days post, but did not affect perceived soreness and muscle damage markers in endurance trained female runners following a single bout of DHR.